Exploring Mental Health Status and Syndrome Patterns Among Young Refugee Children in Germany - Buchmüller, Thimo; Lembcke, Hanna; Busch, Julian; Kumsta, Robert; Leyendecker, Birgit (Frontiers in Psychiatry, 2018)
Refugee children share a large number of pre-, peri-, and post-migration risk factors, which make them vulnerable for developing mental health concerns. Within the last few years, a large number of families with young children have sought refuge in Germany. However, children’s mental health status in Germany is mostly unclear. A central aim of developmental psychopathology is to understand how risk factors lead to the emergence of mental health concerns. One approach to investigating this association is the study of specificity, which describes the idea that specific risk factors are related to specific psychological outcomes. The aim of our study was to assess the mental health status of young refugee children in Germany, and to explore a potential refugee-specific mental health pattern. In two studies, we assessed mental health outcomes of 93 children from Syria or Iraq, aged 1.5 to 5 years, who recently arrived in Germany. The results were compared to U.S. norm data of typically developing children, and to norm data of a clinical sample in order to explore mental health patterns. In the first study (n = 35), we used standardized screening tools for parents (CBCL 1.5-5). In the second study (n = 58), mental health states of refugee children were assessed by caretakers (CTRF 1.5-5). In comparison to U.S. norm data of normally developing children, refugee parents reported more mental health concerns for their children, especially on syndrome scales of internalizing difficulties. A comparison to U.S. clinical reference data showed a specific mental health pattern, characterized by increased levels of anxiety/depression, attention problems, and withdrawal behavior. Caretakers, too, reported more mental health problems compared to typically developing children, albeit to a smaller extent. However, a comparison to clinically-referred children only led to partial confirmation of a specific mental health pattern. Our studies offer important insights into the mental health status and pattern of young refugee children, which is essential for preventing the onset of psychopathology and for offering tailored interventions.